Study on Mechanical Behavior of Slip Zone Soils Under Different Factors—A Case Study - Liu, Kai; Wang, Xingang; Lian, Baoqin; Zhu, Zhaobo; Xue, Chen (Frontiers in Earth Science, 2022)
The mechanical properties of the slip zone soil play an important role in the evolution of the loess landslides. To further understand these characteristics, a series of ring shear tests was conducted on the slip zone soils obtained from Tianshuigou landslide, to investigate the influence of moisture content, dry density, shear rate and shear method on the mechanical characteristics of slip zone soils. The experimental results showed that: an increase in the moisture content of the slip zone loess causes a significant reduction in the residual strength. Specially, both the residual cohesion and residual internal friction angle show a deceasing tendency with moisture content. The change in the residual cohesion is more sensitive to the variation in moisture content. Additionally, a trend that strength increased with the increasing of dry density was observed, and the influence degree of dry density on the increased strength is more pronounced at low moisture contents. Thirdly, shear strength shows a negative relationship with shear rate when the shear rate ranges from 0.01 mm/min and 1 mm/min. When the shear rate increased up to 10 mm/min, a stepped shear band is developed and the strength increased. In addition, the strain-softening phenomenon was observed in the single-stage shear tests, which was not noticed in the multi-stage shear tests and pre-shear tests. The residual strength obtained in pre-shear test and multi-stage shear test is slightly greater than that in the single-stage shear test. The experimental results herein can provide an important basis for analyzing the evolution mechanism and prevention of loess landslides.